Analysis of Social Media Relations to the Decision of Visiting in the Ria Beach Recreation Park of Kenjeran, Surabaya by AISAS Method (Attention, Interest, Search, Action, Share) - Nining Yusnita D. Oktimawati; Mimit Primyastanto; Zainal Abidin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
This research was conducted to know and analyze the impact, the most dominant factor, and social media relations and factors of AISAS (Attention, Interest, Search, Action, Share) on the decision of visiting in the Ria Beach Recreation Park, Kenjeran of Surabaya. The respondents of this research were 30 tourist visitors of old Kenjeran beach and 30 tourist visitors of new Kenjeran beach. This research use descriptive method. The result is that the characteristics of the majority of respondents are 21-25 years, the level of education is high school with employment status as students and majority use instagram. From the test results obtained very biased results is the social media because the majority of tourists stated that social media accounts accessible to the public because social media is the most appropriate media to convey information from the manager to tourists as well as among tourists as a means of tourism promotion beachs do, so many of them are interested in advertising on social media (Interest) and look for further information (Search) then gives rise to the desire for a visit to the old Kenjeran and new Kenjeran beach (Action). Finally, after the tourists had a pleasant impression, they disseminate the experiences (Share) through social media or word of mouth, so they can make information and recommendation by the public to visit.